Rab21-Targeted Nano Drug Delivery System-Based FFPG for Efficient Paclitaxel Delivery to Inhibit Lung Cancer Progression - Jing Wang; Xueying Yan; Wenfei Wang; Shu Wang; Hongxiang Jiang; Xinhua Zhu; Zhehui Li; Defu Cai; Yonggang Xia (Pharmaceutics)
Background/Objectives: Platycodon grandiflorus (PG) has been widely researched as a conductant drug for the treatment of lung diseases by ancient and modern traditional Chinese medicine (TCM) practitioners. Inspired by the mechanism and our previous finding about fructans and fructooligosaccharides from Platycodon grandiflorus (FFPG), we developed a nano drug delivery system (NDDS) targeting lung cancer. The aim was to improve the efficiency of the liposomal delivery of Paclitaxel (PTX) and enhance the anti-tumor efficacy. Methods: The FFPG-Lip-PTX NDDS was prepared by electrostatic adsorption. Dynamic light scattering, zeta potential, and transmission electron microscopy were used for physical characterization. The release behavior of the NDDS was simulated by dialysis. The uptake of the NDDS was observed by confocal microscopy and flow cytometry. Cytotoxicity, apoptosis, migration, and invasion experiments were used to evaluate the anti-tumor ability of the NDDS in vitro. The penetration and inhibition of tumor proliferation were further analyzed via a 3D tumor sphere model. Finally, in vivo biological distribution and pharmacodynamic experiments verified the targeting and anti-tumor ability of the FFPG-Lip-PTX NDDS. Results: FFPG-Lip-PTX possessed a homogeneous particle size distribution, high encapsulation efficiency, and stability. In vitro experiments confirmed that FFPG promoted the uptake of the NNDS by tumor cells and enhanced cytotoxicity. It also increased the anti-tumor effect by promoting cell apoptosis and inhibiting invasion and metastasis. The same conclusion was obtained in 3D tumor spheres. In vivo experiments exhibited that FFPG-lips-PTX showed more significant lung cancer-targeting activity and anti-tumor effects. Conclusions: In this study, a novel lung-targeted NDDS is proposed to enhance the therapeutic effect of chemotherapy drugs on lung cancer.